2005
DOI: 10.1007/s10439-005-5688-9
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory Pressurization of an Animal Cell as a Poroelastic Spherical Body

Abstract: The analytical solution of a spherical poroelastic body under an oscillatory hydrostatic pressurization is obtained. This solution is then parameterized and interpreted in terms of a spherical animal cell with the cytoskeleton serving as the solid phase. It is found that for a cell with free or nearly free membrane leakage (such as in the case of an osteocytic cell body), the induced pore fluid pressure amplitude near the center of the cell exceeds the amplitude of the applied pressure by 50% if the loading fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The effects of hydrostatic pressure on individual cells are complicated by spatial heterogeneity in local cell stiffness; for example, the cell body will deform more than cellular processes under hydrostatic loads, since the cell's body is more compliant than its processes (Docheva et al, 2008). Poroelastic cell models with idealized geometries have been developed to estimate local deformation of a cell under cyclic hydrostatic pressure (Zhang, 2005). Physiological loading also causes strains in whole bone in vivo which are typically in the range of 0.04-0.3% for animal and human locomotion, but seldom exceed 0.1% (Rubin and Lanyon, 1984;Fritton et al, 2000).…”
Section: Forces Experienced By Bone Cellsmentioning
confidence: 99%
“…The effects of hydrostatic pressure on individual cells are complicated by spatial heterogeneity in local cell stiffness; for example, the cell body will deform more than cellular processes under hydrostatic loads, since the cell's body is more compliant than its processes (Docheva et al, 2008). Poroelastic cell models with idealized geometries have been developed to estimate local deformation of a cell under cyclic hydrostatic pressure (Zhang, 2005). Physiological loading also causes strains in whole bone in vivo which are typically in the range of 0.04-0.3% for animal and human locomotion, but seldom exceed 0.1% (Rubin and Lanyon, 1984;Fritton et al, 2000).…”
Section: Forces Experienced By Bone Cellsmentioning
confidence: 99%
“…Poroelasticity has been a popular model to describe the resistance of soft tissues to compression. Only recently, the poroelasticity model was applied to explain various cellular behaviors, such as cell migration [160,161], cell responses to an oscillatory pressure [162], and bleb formation [163][164][165]. It was also suggested that poroelastic parameters may serve as biomarkers for cancer diagnosis and therapies [166].…”
Section: Viscoplasticitymentioning
confidence: 99%
“…One possible approach to modelling such flows is to use poroelasticity theory (e.g. Zhang, 2005;Kimpton et al, 2015;Copos and Guy, 2018), which has been well validated against experiments (Moeendarbary et al, 2013). We incorporate poroelastic effects into the model constructed below.…”
Section: Introductionmentioning
confidence: 99%